Pengaruh Budaya Organisasi dan Program Keselamatan, Kesehatan Kerja (K3) pada Produktivitas Karyawan PT KAI Bandung - Setiawan, Heru (Jurnal Trikonomika, 2009)
Human Resources is one of the most important factor in achieving the company goals. The limited human resources with high competency become one of the company constraint in Indonesia. Goal of this research is to know the influence of organizational culture, and K3 program to PT Kereta Api Persero Bandung employees productivity. This research used descriptive dan verifikatif method. Sampling techniques used simple random sampling with the number of samples equal to 43 respondents. Primary dan secondary data has been used in this research. Multiple regression analysis employed to know the influence of organizational culture, and K3 program to PT Kereta Api Persero Bandung employees productivity. Several statistical test have been used to determine the validity and reliability data, correlation between variable, coefficient determinant, and hypotesis assesstment. The study found that the organizational culture and K3 program significantly have positive effect on employee productivity. However improvement of employees productivity in PT KAI still lower. This happened because still lack of incentive for employees in the form of appreciation and reward.